1987
DOI: 10.1007/bf02535556
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and metabolism of hexadecylphosphocholine in mice

Abstract: Distribution and metabolic fate of radiolabeled hexadecylphosphocholine (He-PC) has been studied in mice. It is demonstrated that He-PC is well-absorbed from the intestinal tract, intravenous (IV) and oral administration lead to similar distributions throughout the body, the highest accumulation of radioactivity occurs in liver, lung and kidney, and the metabolic products are radioactive choline, phosphocholine and 1,2-diacylphosphatidylcholine. The occurrence of these metabolites indicates that phospholipases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 7 publications
3
36
2
2
Order By: Relevance
“…al., 1978;Hoffman et al, 1986;Breiser et al, 1987). At the present time, we believe the most parsimonious hypothesis to be that ATLs are more potent than natural lipids because of their greater metabolic stability.…”
Section: Discussionmentioning
confidence: 75%
“…al., 1978;Hoffman et al, 1986;Breiser et al, 1987). At the present time, we believe the most parsimonious hypothesis to be that ATLs are more potent than natural lipids because of their greater metabolic stability.…”
Section: Discussionmentioning
confidence: 75%
“…In previous studies, we demonstrated that alkylphosphocholines can be applied orally without overt side effects (5,13). After a daily oral application of the alkylphosphocholine He-PC (10 mg/kg) to rats, a steady-state level of about 100 ,uM was obtained in serum (30) (7).…”
Section: Resultsmentioning
confidence: 95%
“…The remarkable activity of He-PC in the spleens and bone marrow of mice might be explained, at least in part, by a favorable distribution of the compound in the reticuloendothelial system (5,18). Specifically, destruction of intracellular amastigotes in the reticuloendothelial system is achieved by activated macrophages; and different cytokines, such as gamma interferon, interleukin-4, or tumor necrosis factor alpha, contribute to the induction of antileishmanial macrophage activation (12,27).…”
Section: Resultsmentioning
confidence: 99%
“…A partir de doses de 30 mg/Kg duas vezes por dia, concentrações de 155 -189 nmol/g de tecido são alcançados (DORLO et al, 2008). A miltefosina é eliminada lentamente, com uma meia-vida de 96 horas (BRESISER et al, 1987). Este fármaco é indicado principamente para o tratamento de leishmaniose visceral em dose de 50 ou 100 mg/Kg em pacientes com menos ou mais de 25 kg respectivamente.…”
Section: Miltefosinaunclassified